Adaptive aberration compensation for three-dimensional micro-fabrication of photonic crystals in lithium niobate. - Cumming, B; Jesacher, A; Booth, M; Wilson, T; Gu, M (2011)
We present the use of a liquid crystal spatial light modulator to correct for the refractive-index mismatch induced spherical aberration in a high refractive-index lithium niobate crystal when a low repetition rate amplified laser is used for the direct fabrication of three-dimensional micro-structures. By correcting the aberration based on experimentally determined values, we show that the size of written structures decreases dramatically, which allows the fabrication of high quality micro-structures such as three-dimensional photonic crystals. We demonstrate that, through the use of adaptive optics, the fabrication depth and the stopgap strength in the corresponding photonic crystals are increased by a factor of two to three.